Evaluating the Quality of Life in Children Aged 10- 16 with Type 1 Diabetes in Yazd: A Comprehensive Assessment of Psychological, Social, and Health-Related Challenges - Mohammad Mehdi Falahati; Nasim Namiranian; Vida Sadat Anoosheh; Masoud Rostami; Farzad Ferdosian; Ahmad Shajari (Iranian Journal of Diabetes and Obesity)
Objective: Type 1 diabetes significantly affects children physical, emotional, social, and academic well-being, reducing their Quality of Life (QoL) and potentially causing psychological problems. This study evaluates the QoL in children aged 10 - 16 with type 1 diabetes in Yazd. Materials and Methods: In this analytical cross-sectional study, 75 children with type 1 diabetes who visited healthcare clinics in Yazd were assessed. Data were collected using a demographic questionnaire and the Pediatric QoL Inventory (PedsQL), QoL questionnaire, evaluating four subscales: physical, emotional, social, and academic performance. Data were analyzed using SPSS -24 software. Results: The highest QoL score was in the physical dimension (mean: 8.51 (± 7.04)), while the lowest was in academic performance (mean: 4.02 (± 3.75)). A significant relationship was found between gender and academic performance (girls: 2.43 (± 1.58), boys: 1.93 (± 1.04)) (P= 0.021). HbA1C levels significantly correlated with academic (P= 0.028) and social (P= 0.013) dimensions. Parental education (father: P= 0.007, mother: P= 0.047) and employment status (father: P= 0.039, mother: P= 0.025) were also associated with QoL and academic performance. Conclusion: Type 1 diabetes particularly impacts the academic and social dimensions of QoL in children, potentially leading to long-term psychological consequences. Further research should explore therapeutic, educational, and familial interventions to enhance their QoL.